Trade Openness and Gender Discrimination - Helena Santos, Marina; Arbache, Jorge Saba (World Bank, Washington, DC, 2017)
This paper investigates the impact of trade liberalization on gender wage discrimination. The authors employ a simple method that is able to capture the direct impacts of openness at the industry level on the gender wages. The authors find evidence that increasing openness is associated with narrowing wage gap, which results mainly from men’s wages declining. This is consistent with the Becker’s (1957) proposition that competition reduces discrimination in the labor market. The plan of the paper is as follows : 1) Section one introduces; 2) Section two presents the trade liberalization in Brazil; 3) Section three presents the data, strategy and results; and 4) Section four concludes.